Fisher, Susan T. (Mrs. Galen), residential, Oakland (built 1910) - James H. Edelen::::::photographer:::
Fisher, Susan T. (Mrs. Galen), residential, Oakland, Job # 280, 1910. Photograph by James Edelen.